PRECEDENT SOURCES OF ALLUSIVE TITLES IN FICTION AND NEWSPAPER TEXTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Allusive titles serve as a significant vehicle for intertextuality, enriching the meaning and resonance of fiction and newspaper texts. This study examines the precedent sources of allusive titles, focusing on their origins, functions, and implications for readers. By analyzing examples from literary works and journalistic headlines, the research highlights how such titles draw from cultural, historical, religious, and literary references to establish connections with prior texts and contexts. This paper also explores the role of allusion in shaping audience interpretations and enhancing textual engagement. The findings underscore the importance of precedent phenomena in understanding the layered meanings of allusive titles.